2011
DOI: 10.4103/0972-0707.80733
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-enriched mixture pulpotomy of a human permanent molar with irreversible pulpitis and condensing apical periodontitis

Abstract: This case report describes a pulpotomy treatment of a permanent mature molar tooth with established irreversible pulpitis and condensing apical periodontitis, using calcium-enriched mixture (CEM) cement. Clinical examination revealed that the first right lower molar had a large carious lesion with history of spontaneous/lingering pain; radiographic examination showed condensing apical periodontitis. Pulpotomy was opted as the treatment; cervical pulpotomy was carried out. Following hemostasis, the radicular pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…Finally, 31 articles were included: 15 case reports or case series (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 9 cohort studies (15,(31)(32)(33)(34)(35)(36)(37)(38), and 3 clinical trials and 4 randomized clinical trials (39)(40)(41)(42)(43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 31 articles were included: 15 case reports or case series (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 9 cohort studies (15,(31)(32)(33)(34)(35)(36)(37)(38), and 3 clinical trials and 4 randomized clinical trials (39)(40)(41)(42)(43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, recent reports have demonstrated that teeth with irreversible pulpitis showed favorable treatment outcomes with pulpotomy using CEM/MTA as pulp cappings. [357] Though the diseased pulps in these cases were inflamed, they were still vital; that is they still maintained a blood supply and therefore the most important factor for healing. In the light of recent high-level evidences,[7] the inflammatory process should be re-examined to recognize its possible or probable positive effect on pulpal healing.…”
Section: Discussionmentioning
confidence: 99%
“…[12] An in vitro study revealed that the anti-bacterial properties of CEM are similar to calcium hydroxide. [13] CEM has been employed as a root-end filling material,[14] as well as direct pulp capping agent,[15] pulpotomy agent,[561617] apical plug,[18] in the repair of furcal perforations,[19] management of root resorption,[20] and regenerative endodontics. [21] Recently, an interesting report demonstrated favorable treatment outcomes of direct pulp capping with CEM for management of a permanent mature molar with irreversible pulpitis and associated apical periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…[84] In a case series study of 12 permanent mature molars with irreversible pulpitis, CEM was used for pulpotomy, and resulted in complete success at a follow-up after16 months. It was also shown that to enable improved regeneration, the pulp-dentin complex had isolated itself by forming a calcified bridge.…”
Section: Full/complete Pulpotomy With Cem Cementmentioning
confidence: 99%